2009
DOI: 10.1002/jmri.21654
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive monitoring of a murine model of metastatic pheochromocytoma: A comparison of contrast‐enhanced microCT and nonenhanced MRI

Abstract: Purpose To compare contrast-enhanced micro computed tomography (microCT) and non-enhanced respiratory-triggered MRI in an animal model of metastatic pheochromocytoma. Animal models are becoming important in the study of cancer treatment and imaging is useful in minimizing the number of animals needed and reducing costs associated with autopsies. However, the choice of imaging modality is still evolving. Materials and Methods Adult female nude mice were injected by tail vein with a mouse pheochromocytoma (MPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…The metastatic mouse pheochromocytoma model used in this study was previously described (22, 30). Briefly, female 6-8 week old (20-22 g) athymic nude mice (NCr-nu; Taconic, Germantown, NY) were injected by tail vein with 1×10 6 MPC (MPC 4/30 PRR) cells.…”
Section: Methodsmentioning
confidence: 99%
“…The metastatic mouse pheochromocytoma model used in this study was previously described (22, 30). Briefly, female 6-8 week old (20-22 g) athymic nude mice (NCr-nu; Taconic, Germantown, NY) were injected by tail vein with 1×10 6 MPC (MPC 4/30 PRR) cells.…”
Section: Methodsmentioning
confidence: 99%
“…This accuracy in small tumor detection [5,7,8,10,14,15,22] is an advantage of using CT [22] for longitudinal evaluation of tumors. However, MRI using magnetic fields is assumed to be a harmless imaging procedure [20][21][22][23][24][25] even if newly controversial, [30,31] whilst CT, an X-raybased approach, raises concerns about immunological and general physiological changes that might affect the experimental outcome [32].…”
Section: Discussionmentioning
confidence: 99%
“…Small animal imaging technologies have been already extensively applied for liver imaging using CT or MRI [20][21][22] at a lesser degree, but not for pancreas. Few MRI [23][24][25] and one CT studies [16] for pancreatic tumor detection in mice are available in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that, in addition to the advantages of not exposing the animal to ionizing radiation, MRI provides a more complete assessment. 15 In contrast, micro-CT imaging can be performed easily and also allows for functional studies, while also being readily implemented in animal facilities.…”
mentioning
confidence: 99%